Microbiome in cancer: An exploration of carcinogenesis, immune responses and immunotherapy - Zhou, Pei; Hu, Yawen; Wang, Xiaoyan; Shen, Luxuan; Liao, Xinghao; Zhu, Yajuan; Yu, Jiadong; Zhao, Fulei; Zhou, Yi; Shen, Hengshui; Li, Jiong (Frontiers in Immunology, 2022)
Cancer is a major disease endangering human health. More and more studies have shown that microorganisms play an extremely important role in the occurrence, development and treatment of tumors. As a very promising tumor treatment strategy, immunotherapy has also been proved to have a great relationship with microorganisms. Here, the authors review the contribution of the microbiota to cancer and the research on its impact on cancer immunotherapy. We also highlight the possible mechanism of their interaction and outlined the potential application of microbiota in tumor immunotherapy.